Svenska Akademiens ordbok har passerat S! - Sigurd, Bengt (LexicoNordica, 2003)
A new volume (nr 33) of the Dictionary of the Swedish Academy has been published. The dictionary is known for its long time of publication - it was started in 1892 and has just reached the letter T - and the review article gives a survey of the history of this unique project and comments on the latest volume. It is observed that the articles keep to the standards of the previous volumes and that it is hard to find any missing words, missing meanings or mistakes. The future of the dictionary has recently been discussed because of financial and editorial problems. It is difficult to find and keep an expert staff of editors these days. The Swedish Academy has now decided that the dictionary is to be finished by 2017.